N-Methyl-d-Aspartate Receptor – Nitric Oxide Synthase Pathway in the Cortex of Nogo-A-Deficient Rats in Relation to Brain Laterality and Schizophrenia - Kristofikova, Zdena; Vrajova, Monika; Sirova, Jana; Vales, Karel; Petrasek, Tomas; Schönig, Kai; Tews, Bjorn; Schwab, Martin; Bartsch, Dusan; Stuchlik, Ales; Ripova, Daniela (Frontiers in Behavioral Neuroscience, 2013)
It has been suggested that Nogo-A, a myelin-associated protein, could play a role in the pathogenesis of schizophrenia and that Nogo-A-deficient rodents could serve as an animal model for schizophrenic symptoms. Since changes in brain laterality are typical of schizophrenia, we investigated whether Nogo-A-deficient rats showed any signs of disturbed asymmetry in cortical N-methyl-D-aspartate (NMDA) receptor–nitric oxide synthase (NOS) pathway, which is reported as dysfunctional in schizophrenia. In particular, we measured separately in the right and left hemisphere of young and old Nogo-A-deficient male rats the expression of NMDA receptor subunits (NR1, NR2A and NR2B in the frontal cortex) and activities of NOS isoforms (neuronal (nNOS), endothelial (eNOS) and inducible (iNOS) in the parietal cortex). In young controls, we observed right/left asymmetry of iNOS activity and three positive correlations (between NR1 in the left and NR2B laterality, between NR2B in the right and left sides, and between NR1 in the right side and nNOS laterality). In old controls, we found bilateral decreases in NR1, an increase in NR2B in the right side and two changes in correlations in the NR1–nNOS pathway. In young Nogo-A-deficient rats, we observed an increase in iNOS activity in the left hemisphere and two changes in correlations in NR1–nNOS and NR2A–eNOS, compared to young controls. Finally, we revealed in old Nogo-A-deficient animals, bilateral decreases in NR1 and one change in correlation between eNOS–iNOS, compared to old controls. Although some findings from schizophrenic brains did not manifest in Nogo-A-deficient rats (e.g., no alterations in NR2B), others did (e.g., alterations demonstrating accelerated ageing in young but not old animals, those occurring exclusively in the right hemisphere in young and old animals and those suggesting abnormal frontoparietal cortical interactions in young animals).